(untitled) (Bangladesh Medical Journal, 2023)
Myocardial Infarction is one of the most common causes of mortality and morbidity among the elderly patients. Also, it is known for wide range of clinical presentations other than chest pain. Yet, a large number of patients may have atypical or no symptoms. As an indication of a cardiac problem, resulting in a delay in seeking medical care the absence of typical chest pain and the vagueness of symptoms might not be recognized. The absence of typical chest pain and the vagueness of symptoms might not be recognized. This cross sectional observational study was carried out among 50 patients >60 years of either sex with acute myocardial infarction in the Department of Medicine and CCU of Dhaka Medical College Hospital, Dhaka, from January 2018 to July 2018. Then consent was taken. History taking and physical examination were done in a predesigned data collection sheet. Then required investigation like ECG, cardiac enzymes and relevant laboratory investigations was done. After collecting all available information statistical analysis was done using SPSS for windows version 20. Result was expressed as frequency, percentage, mean (±SD), range, p-value. Among the 50 patients diagnosed as having AMI, 14 (28%) patients presented with atypical presentation to the hospital. Atypically presenting AMI Patients were mostly ae group 60-69 years (50%). Among all patients 29 (58%) were male and 21(42%) were female. 14 (28%) patients had no complaints of chest pain, out of which, dyspnea and epigastric pain (28.6%) are the commonest. Atypical presentation is found in 38.1% of female elderly patients and 20.7% of male patients (p=0.002). Commonest risk factor, found in this study was hypertension (66%) of the patients included in the study. Next common was Diabetes Mellitus (64%), hypercholesterolemia (56%) and smoking (28%). 13 Patients with Diabetes presented with atypical symptoms among atypical group (p=0.008). Most of the patients with atypical symptoms (78%) presented lately more than 12 hours compared to patients with typical symptom. Mortality rate was higher among the patient presented with atypical symptoms (42.3%) than among the patients presented with typical chest pain (27.7%). 28% patient with atypical chest pain was found to have inferior MI and mortality was highest among those with inferior MI and atypical symptoms. This study showed that even though chest pain was the most common presentation in elderly AMI patients, they were also found to have atypical presentations like dyspnea, vomiting, sweating and epigastric pain. This signifies the need of examining physicians to meticulously identify acute myocardial infarction in elderly for successful and immediate treatment. Accurate diagnosis of ACS could reduce hospital mortality and morbidity. Bangladesh Med J. 2022 May; 51(2): 13-20